2016
DOI: 10.1002/cmdc.201600236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ebsulfur Analogues with Broad‐Spectrum Antifungal Activity

Abstract: Invasive fungal infections are on the rise due to an increased population of critically ill patients as a result of HIV infections, chemotherapies, and organ transplantations. Current antifungal drugs are helpful, but insufficient in addressing the problem of drug-resistant fungal infections. Thus, there is a growing need for novel antimycotics that are safe and effective. The ebselen scaffold has been evaluated in clinical trials and has been shown to be safe in humans. This makes ebselen an attractive scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…30-32 Universally, eukaryotic cells produce basal amount of ROS in mitochondria as a byproduct of cellular metabolism. In response, the cellular enzymatic antioxidants, including superoxide dismutase and glutathione peroxidase, scavenge ROS in cells.…”
Section: Resultsmentioning
confidence: 99%
“…30-32 Universally, eukaryotic cells produce basal amount of ROS in mitochondria as a byproduct of cellular metabolism. In response, the cellular enzymatic antioxidants, including superoxide dismutase and glutathione peroxidase, scavenge ROS in cells.…”
Section: Resultsmentioning
confidence: 99%
“…In an intensive search for non-antifungal drugs exhibiting antifungal activity, we and others [2224] demonstrated that ebselen possesses potent broad-spectrum fungicidal activity against Candida and Cryptococcus spp with the MIC values ranging from 0.5 to 2 μg/ml. Although, its antifungal activity has been reported before, the antifungal mechanism of action and in vivo efficacy of ebselen remains unclear with several potential targets proposed [17,2224]. In the present study, we demonstrated that ebselen reduces GSH concentration in yeast cells leading to dysregulation of redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with a recent study by Ngo et. al that demonstrated ebselen treatment induces ROS in Candida albicans [22]. In addition, Azad et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2127 There are examples of 2,4-difuoro-2-(1 H -1,2,4-triazo-1-yl)acetophenone analogues with linear C 5 –C 8 alkyl chains 25 and of an n -alkylated ebsulfur derivative with a linear C 5 alkyl chain, which displayed strong antifungal activity. 24 Similarly, examples of aminoglycosides ( e.g. , kanamycin B (KANB) and tobramycin (TOB)) with linear alkyl chains with 12 and 14 carbons (C 12 and C 14 ) displaying antifungal activity were also reported.…”
Section: Introductionmentioning
confidence: 99%